2017
DOI: 10.1002/elsc.201700045
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the influence of microstructured surfaces on the lactic acid production of Lactobacillus delbrueckii lactis in a flow‐through cell system

Abstract: Microorganisms growing in biofilms might be possible biocatalysts for future biotechnological production processes. Attached to a surface and embedded in an extracellular polymeric matrix, they create their preferred environment and form robust cultures for continuous systems. With the objective of implementing highly efficient processes, productive biofilms need to be understood comprehensively. In this study, the influence of microstructured metallic surfaces on biofilm productivity was researched. To conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Previous studies on other microorganisms have proven an influence of the surface topography and/or the material used on attachment and growth, as well as production of compounds by biofilms [21,35,36]. Furthermore, Singh et al [37] suggested a relationship between surface roughness and bacterial attachment in that they are inversely related beyond a specific threshold.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on other microorganisms have proven an influence of the surface topography and/or the material used on attachment and growth, as well as production of compounds by biofilms [21,35,36]. Furthermore, Singh et al [37] suggested a relationship between surface roughness and bacterial attachment in that they are inversely related beyond a specific threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on other microorganisms have proven an influence of the surface topography and/or the material used on attachment and growth, as well as production of compounds by biofilms . Furthermore, Singh et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All flow cell design parameters and operational settings were identical to those described previously . Briefly, flow cells were constructed with a flow channel volume of 8.75 mL and either a smooth (S) or microetched (ME) bottom surface as a substrate for the attachment of cells and development of a biofilm.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, flow cells were constructed with a flow channel volume of 8.75 mL and either a smooth (S) or microetched (ME) bottom surface as a substrate for the attachment of cells and development of a biofilm. Micro‐etching of the flow cell surface was conducted in response to previous results indicating that ME surfaces promoted the development of L. delbrueckii lactis biofilm . During biofilm cultivation, each flow cell (ME and S) was run in a continuous loop to a separate reservoir (MRS medium, pH 7.0, 45°C) for 24 h at a flow rate of 5 mL/min in intervals of 15 min on and 60 min off.…”
Section: Methodsmentioning
confidence: 99%